Korelasi Asas Equality Before the Law dengan Affirmative Action dalam UU No. 7 Tahun 2017 tentang Pemilihan Umum: Studi Kritis atas Kuota 30% Keterwakilan Perempuan - Muh Akbar Yanlua; Mohammad Sarfan Basyir Putuhena; Syah Awaluddin (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the correlation between the principle of equality before the law and the affirmative action policy, which is expressed in the form of a 30% quota for women's representation in the political field, as stipulated in Law Number 7 of 2017 concerning General Elections. The focus of the study is directed at the extent to which this quota policy is in line with the principle of equality before the law and reflects substantive justice in democratic practices in Indonesia. The research method used is normative research by examining laws and regulations, legal doctrine, and relevant literature. This approach is used to assess whether the quota policy for women's representation is in accordance with the constitutional principle of equality, while also considering the challenges of its implementation in a socio-political context that is still gender biased. The results of the study indicate that the 30% quota for women in legislative candidacy is a form of positive discrimination intended to correct structural and historical inequalities in women's political participation. This policy is expected to open wider spaces for participation so that women have equal opportunities to play a role in the legislative process and public policy making. However, this policy has also drawn criticism. Some believe that the quota emphasizes fulfilling numbers rather than the quality and capacity of the individuals nominated. Therefore, the quota must be accompanied by efforts to improve the quality of women's human resources, political education, and transparent, merit-based selection mechanisms. This way, women's representation will not only be formal but also substantial and contribute significantly to democratic development. In conclusion, the 30% quota policy remains necessary as an affirmative step toward de facto equality. However, strengthening capacity and supporting systems is crucial for its implementation to align with the principle of equality before the law and achieve substantive justice.